2012
DOI: 10.1007/s10517-012-1722-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Reaction to a Titanium-Nickelide Mesh Implant after Plasty of Postresection Defects of Anatomic Structures of the Chest

Abstract: We studied morphological features of the regenerate formed after postresection defect plasty of the pericardium, diaphragm, and thorax with a mesh implant made of nanostructural titanium-nickelide threads. The newly formed tissue grew through the implant with the formation of an integrated tissue regenerate ensuring anatomic and physiological restoration of this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In general they leave the nest in the order of hatching one by one at intervals of about one day and fledging period is longer the bigger the brood [ 31 ]. Fledglings reach independence 5–9 weeks after fledging [ 36 , 37 , 46 , 47 ]. Wing length of nestlings continues to grow with age from hatching until the period after fledging (owlets fledge with incomplete feather growth), while body weight increases only to 3–4 weeks after hatching, and thereafter is essentially stable or may even decline [ 31 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general they leave the nest in the order of hatching one by one at intervals of about one day and fledging period is longer the bigger the brood [ 31 ]. Fledglings reach independence 5–9 weeks after fledging [ 36 , 37 , 46 , 47 ]. Wing length of nestlings continues to grow with age from hatching until the period after fledging (owlets fledge with incomplete feather growth), while body weight increases only to 3–4 weeks after hatching, and thereafter is essentially stable or may even decline [ 31 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the first TNM iv vivo animal test for post-resection abdominal defect management in the EU. So far, only a knitted TNM implant has been successfully applied for plasty of post-resection defects of the pericardium, diaphragm and chest wall in a dog model [9]; some doubtful clinical studies have been reported in Russian periodicals [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases after ingrowth and maturation of the connective tissue, they become rigid, and their plasticization and changes in size disturb the biomechanics of anatomical structures. Moreover, synthetic meshes are very liable to the persistence of infection; in the case of purulent post-operative complications they maintain inflammation and complicate clearance of the focus of suppurative inflammation [9]. Also, in some cases, an implant can be rejected even without a prominent inflammatory reaction [10].…”
Section: Introductionmentioning
confidence: 99%